Surveillance of Hepatocellular Carcinoma in Nonalcoholic Fatty Liver Disease - Yoshio Sumida; Masashi Yoneda; Yuya Seko; Hiroshi Ishiba; Tasuku Hara; Hidenori Toyoda; Satoshi Yasuda; Takashi Kumada; Hideki Hayashi; Takashi Kobayashi; Kento Imajo; Masato Yoneda; et al. (Diagnostics, 2020)
Nonalcoholic fatty liver disease (NAFLD) is becoming the leading cause of hepatocellular carcinoma (HCC), liver-related mortality, and liver transplantation. There is sufficient epidemiological cohort data to recommend the surveillance of patients with NAFLD based upon the incidence of HCC. The American Gastroenterology Association (AGA) expert review published in 2020 recommends that NAFLD patients with cirrhosis or advanced fibrosis estimated by non-invasive tests (NITs) consider HCC surveillance. NITs include the fibrosis-4 (FIB-4) index, the enhanced liver fibrosis (ELF) test, FibroScan, and MR elastography. The recommended surveillance modality is abdominal ultrasound (US), which is cost effective and noninvasive with good sensitivity. However, US is limited in obese patients and those with NAFLD. In NAFLD patients with a high likelihood of having an inadequate US, or if an US is attempted but inadequate, CT or MRI may be utilized. The GALAD score, consisting of age, gender, AFP, the lens culinaris-agglutinin-reactive fraction of AFP (AFP-L3), and the protein induced by the absence of vitamin K or antagonist-II (PIVKA-II), can help identify a high risk of HCC in NAFLD patients. Innovative parameters, including a Mac-2 binding protein glycated isomer, type IV collagen 7S, free apoptosis inhibitor of the macrophage, and a combination of single nucleoside polymorphisms, are expected to be established. Considering the large size of the NAFLD population, optimal screening tests must meet several criteria, including high sensitivity, cost effectiveness, and availability.